Leopardi a Pisa: Il risorgimento - Spaggiari, William (Rivista Internazionale di Studi Leopardiani, 2022)
After a long silence, Giacomo Leopardi’s return to poetry, during his stay in Pisa (November 1827-June 1828), is related to the preparation of his poetic Crestomazia; the selection of texts involves a re-examination of the literary tradition. In the same period, Leopardi reads Alessandro Manzoni’s civil and religious poems, which for various reasons (such as their metric configuration) bear an influence on the composition of Il risorgimento (April 1828).